Kadar Trigliserida dan Asam Urat pada Peminum Alkohol (Etanol) - Lestari, Fitriana Yeni; Mu’awanah, Isnin Aulia Ulfah; Aryani, Titin (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2025)
Alcohol (ethanol) is a beverage that contains addictive substances which can lead to dependency and addiction. Alcohol consumption disrupts fat metabolism by increasing lipolysis in adipose tissue and causing the accumulation of ectopic fat in the liver that can result in fatty liver disease and an increase in triglyceride levels. Alcohol consumption is associated with an increase in uric acid levels because ethanol and purines in alcohol stimulate the production of uric acid in the blood. This study aims to determine the relationship between alcohol consumption and the levels of triglycerides and uric acid in alcohol consumers in Tirtorahayu Village, Kulon Progo Regency. The research design was experimental with a descriptive observational quantitative analytic approach. The sample consisted of 17 male participants aged 20–60 years. The statistical tests conducted were the Shapiro-Wilk test to assess the normality of the sample distribution and the Spearman’s rho correlation test to examine the relationship between alcohol consumption and the levels of triglycerides and uric acid. The results of the tests indicated that there was no significant relationship between the frequency of alcohol consumption and triglyceride levels (p=0.836, or p>0.05) and uric acid levels (p=0.889, or p>0.05). Additionally, no significant relationship was found between the duration of alcohol consumption and triglyceride levels (p=0.146, or p>0.05) and uric acid levels (p=0.374, or p>0.05). However, a significant relationship was found between the volume of alcohol consumption and both triglyceride levels (p=0.035, or p<0.05) and uric acid levels (p=0.038, or p<0.05). It can be concluded that there is no relationship between the frequency and duration of alcohol consumption and the levels of triglycerides and uric acid. However, there is a relationship between the volume of alcohol consumption and the levels of triglycerides and uric acid.